PENGARUH LITERASI DIGITAL DAN TEMAN SEBAYA TERHADAP HASIL BELAJAR EKONOMI BISNIS SISWA KELAS XI JURUSAN BISNIS DIGITAL DI SMK NEGERI 4 SURABAYA - Hardiyanti Rukmana; Septyan Budy Cahya (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
This research raises the issue of digital literacy and peer interaction among students. The purpose of this study was to observe and explain the effect of digital literacy and peers on the learning outcomes of business economics class XI students majoring in Digital Business at SMK Negeri 4 Surabaya. This research uses descriptive quantitative research. This study has a subject, namely class XI students of the Digital Business Department Class of 2023/2024 at SMK Negeri 4 Surabaya who have taken Business Economics lessons with a total of 102 respondents. This research was obtained by distributing questionnaires to students and conducting interviews with the head of the digital business department. This study analyzed data using the classical assumption test and multiple linear regression test. The results of this study found that digital literacy has an effect on business economics learning outcomes, peers have no effect on business economics learning outcomes, and digital literacy and peers do not simultaneously affect the learning outcomes of class XI students majoring in Digital Business at SMK Negeri 4 Surabaya.